An inorganic composite membrane for natural gas denitrification and preparation method thereof
By combining the two-dimensional porous carbon nanosheets with the α-Al3O4 ceramic base liner support layer, an inorganic composite film for natural gas denitrogenation was prepared, which solved the problem of insufficient application of the prior art in the field of natural gas denitrogenation, and achieved a high selectivity and permeability gas separation effect.
Patent Information
- Application Number
- CN202210443862.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-04-26
AI Technical Summary
The application of the existing technology in the field of natural gas denitrification has not yet made progress, and research on two-dimensional porous carbon nanosheet materials in this field still needs to be enriched.
A two-dimensional porous carbon nanosheet was combined with an α-Al3O4 ceramic base liner support layer, and a two-dimensional porous carbon nanosheet precursor solution was loaded by a variable temperature and heat immersion method, and an inorganic composite film with selective permeability was prepared after carbonization treatment.
The selectivity and permeability of the inorganic composite membrane are improved, the separation effect on CH4 and N2 is enhanced, and the absence of mechanical strength and separation effect of polymer film and mixed matrix membrane is avoided.
Smart Images

Figure CN116987428B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of inorganic composite membranes, and in particular to an inorganic composite membrane for denitrification of natural gas and a preparation method thereof. Background Art
[0002] Natural gas is one of the most important energy sources in the world. Due to its high calorific value and low pollution, it is widely used in various fields, especially in the fuel and chemical fields. The main component of natural gas is methane (CH4). In the process of natural gas extraction, the presence of impurities such as N2 reduces its calorific value. At the same time, a large amount of energy is consumed during transportation and collection, and it cannot be directly used in production and life. Therefore, natural gas denitrification is a precursor condition for achieving efficient utilization of natural gas.
[0003] Two-dimensional porous carbon nanosheets are a type of graphene-like two-dimensional material with a high aspect ratio, a rigid interface, and a microporous structure with adjustable pore size on the surface. In recent years, they have been widely used in adsorption, catalysis and other fields. However, their application in the field of natural gas denitrification has not made any progress, and related research needs to be enriched. Summary of the invention
[0004] The present invention provides an inorganic composite membrane for natural gas denitrification and a preparation method thereof, comprising a two-dimensional porous carbon nanosheet and an α-Al3O4 ceramic substrate support layer. The two-dimensional porous carbon nanosheet has structural characteristics such as a high aspect ratio, a rigid interface, and a microporous structure on the surface. Through molecular sieving, the two-dimensional porous carbon nanosheet has selective permeability to CH4 and N2, thereby improving the selectivity of the inorganic composite membrane. At the same time, due to the porous structure of the two-dimensional porous carbon nanomaterial itself, the gas transmission resistance of CH4 is small, and the membrane thickness is thin, thereby improving the permeability of the inorganic composite membrane.
[0005] The technical solution of the present invention is as follows:
[0006] An inorganic composite membrane for natural gas denitrification comprises a two-dimensional porous carbon nanosheet and an α-Al3O4 ceramic liner support layer.
[0007] Preferably, the two-dimensional porous carbon nanosheets include one or more of porous heteroatom-doped carbon nanosheets, porous carbon nanosheet composites, porous vertically aligned carbon nanosheets and embedded transition metal nanosheets.
[0008] A method for preparing an inorganic composite membrane for denitrification of natural gas comprises the following steps:
[0009] S1, preparation of two-dimensional porous carbon nanosheet precursor solution;
[0010] S2, pretreatment of the α-Al3O4 ceramic substrate support layer; grinding the surface of the α-Al3O4 ceramic substrate support layer until it is flat under an electron microscope without obvious defects or protrusions; washing it with a pH 3-4 HCl solution and a pH 8-9 NaOH solution for 30-60 minutes each, and then calcining it for 6-10 hours; removing impurities on the surface and inside of the ceramic substrate support layer;
[0011] S3, cooling the pretreated α-Al3O4 ceramic substrate support layer, heating it to 100-170°C, keeping it for 1-3 hours, taking it out, and quickly immersing it in a uniformly dispersed two-dimensional porous carbon nanosheet precursor solution for 10-30 seconds, slowly pulling it up, and repeating the immersion and pulling up for 2-5 times, drying it at 50-70°C for 1-2 hours, and curing it at 100-170°C for 3-6 hours to obtain an initial film;
[0012] S4, carbonizing the initial membrane to obtain an inorganic composite membrane for natural gas denitrification containing two-dimensional porous carbon nanosheets.
[0013] Preferably, in S1, the two-dimensional porous carbon nanosheet precursor solution is a resorcinol formaldehyde resin precursor solution, and the preparation method thereof is:
[0014] S1.1, dissolving poloxamer F127 in an appropriate amount of water at 40-60°C, stirring for 1-3h until uniformly mixed, to obtain a poloxamer F127 solution; dissolving resorcinol and aldehyde in an appropriate amount of water, and mixing the poloxamer F127 solution with the water and stirring evenly; then, adding amine, stirring at a uniform speed, and the solution turns white within 0.5-2.5h; adding ammonia solution with a concentration of 1.5-3.0M to the white solution, heating to 80-90°C, stirring for 4-8h, to obtain a first solution; wherein, poloxamer F127: resorcinol: propylamine: formaldehyde: ammonia solution: water = (0.1-0.5g): (0.22-1.1g): (0.03-0.15g): (0.292-1.46ml): (5-25ml): (390-1950ml); the first solution is a resorcinol formaldehyde resin precursor solution;
[0015] S1.2, take the following raw materials respectively by weight: 100-500 parts of 0.1-0.3 mol / L K4[Fe(CN)6] solution, 30-40 parts of the first solution in S1.1, and 3-10 parts of an iron-based organosilicon precursor;
[0016] S1.3, mixing and stirring the raw materials described in S1.2 in a water bath at 30°C to 50°C for 4h to 5h to obtain a second solution;
[0017] S1.4, filtering the second solution 1 to 5 times using a PTFE filter membrane with a pore size of 0.22 nm to 0.52 nm, then washing with water until the pH value is 6 to 7, and collecting the precipitate;
[0018] S1.5, mixing the precipitate with a NN dimethylformamide (DMF) solution to obtain a 0.1-10 wt. % third solution; the third solution is the two-dimensional porous carbon nanosheet composite material precursor solution.
[0019] Preferably, the preparation method of the iron-based organosilicon precursor is: add 50-70 parts of methylvinylcyclosiloxane, 0.05-0.56 parts of vinylferrocene, 10-15 parts of 2-propenylphenol, and 220-260 parts of NN dimethylformamide (DMF) in a closed high-pressure reactor, stir evenly and heat to 60-70°C at the same time, add 0.33-0.79 parts of benzoyl peroxide, react for 1-4 hours, and obtain the iron-based organosilicon precursor.
[0020] Preferably, the initial film carbonization condition of S4 is to maintain the temperature at 500-800° C. for 2-5 hours in an argon atmosphere.
[0021] Preferably, in S2, when grinding the α-Al3O4 ceramic substrate support layer, 800# and 1500# sandpapers are used successively for grinding.
[0022] Preferably, in S3, the uniformly dispersed two-dimensional porous carbon nanosheet precursor solution is a uniformly dispersed two-dimensional porous carbon nanosheet precursor solution by ultrasonic dispersion.
[0023] Preferably, the partial reaction mechanism equation of the iron-based organosilicon precursor is:
[0024]
[0025] The advantages of the present invention over the prior art are: the inorganic composite membrane for natural gas denitrification and the preparation method thereof, the two-dimensional porous carbon nanosheet precursor is loaded onto an α-Al3O4 ceramic substrate support layer in a certain proportion by a variable temperature hot impregnation method, and an inorganic composite membrane containing the two-dimensional porous carbon nanosheet is prepared by carbonization. The two-dimensional porous carbon nanosheet has a rigid interface due to its high aspect ratio, and has structural characteristics such as a microporous structure on the surface. Through molecular sieving, it has selective permeability to CH4 and N2, thereby improving the selectivity of the inorganic composite membrane; at the same time, due to the porous structure of the two-dimensional porous carbon nanomaterial itself, the gas transmission resistance of CH4 is small, and the membrane thickness is thin, about 5 to 10 μm; the specific surface area of the two-dimensional porous carbon nanosheet is 775.72 m2 / g, the microporosity is 95 to 98%, and the average pore size is about 0.58 nm; thereby improving the permeability of the inorganic composite membrane. Compared with polymer membranes and mixed matrix membranes, inorganic composite membranes with α-Al3O4 ceramic as the substrate are not affected by the trade-off effect, have higher mechanical strength and better separation effect. α-Al3O4 ceramic as the substrate is used because of its high temperature resistance. It is formed with two-dimensional porous carbon nanosheets in one step to make a two-dimensional porous carbon nanosheet inorganic composite membrane. Compared with the preparation of mixed matrix membranes, it avoids the defects of uneven dispersion and phase separation of two-dimensional porous carbon nanosheets in the membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the α-Al3O4 ceramic liner support layer after pretreatment in Example 4 of the inorganic composite membrane for natural gas denitrification and the preparation method thereof according to the present invention;
[0027] Figure 2 This is a SEM image of a sample obtained by directly coating a two-dimensional porous carbon nanosheet precursor solution on an α-Al3O4 ceramic substrate support layer and carbonizing it in Example 4 of the inorganic composite membrane for natural gas denitrification and the preparation method thereof of the present invention;
[0028] Figure 3 is a SEM image of the surface of the inorganic composite membrane containing two-dimensional porous carbon nanosheets in Example 4 of the inorganic composite membrane for natural gas denitrification and the preparation method thereof according to the present invention;
[0029] Figure 4 is an X-ray diffraction pattern of the surface of the two-dimensional porous carbon nanosheet inorganic composite membrane in Example 4 of the inorganic composite membrane for natural gas denitrification and the preparation method thereof according to the present invention;
[0030] Figure 5 This is a diagram of the selectivity-permeability performance of the two-dimensional porous carbon nanosheet inorganic composite membrane in Example 4 of the inorganic composite membrane for natural gas denitrification and the preparation method thereof according to the present invention. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention is described in more detail below in conjunction with the accompanying drawings and specific embodiments.
[0032] Example 1
[0033] An inorganic composite membrane for natural gas denitrification comprises a two-dimensional porous carbon nanosheet and an α-Al3O4 ceramic liner support layer.
[0034] Preferably, the two-dimensional porous carbon nanosheets include one or more of porous heteroatom-doped carbon nanosheets, porous carbon nanosheet composites, porous vertically aligned carbon nanosheets and embedded transition metal nanosheets.
[0035] The two-dimensional porous carbon nanosheet precursor solution is at least a precursor solution of porous vertically arranged carbon nanosheets. Porous heteroatom-doped carbon nanosheets refer to the process of preparing a hydroquinone formaldehyde resin precursor solution, in which a solution containing heteroatoms is adjusted and added for heteroatom doping. Porous carbon nanosheet composites and embedded transition metal nanosheets are obtained by modifying the hydroquinone formaldehyde resin precursor solution after preparation. Porous carbon nanosheet composites are obtained by preparing a porous vertically arranged carbon nanosheet precursor and reacting it with K4[Fe(CN)6].
[0036] Due to its high aspect ratio, rigid interface and microporous structure on the surface, the two-dimensional porous carbon nanosheets have selective permeability to CH4 and N2 through molecular sieving, thus improving the selectivity of the inorganic composite membrane. At the same time, due to the porous structure of the two-dimensional porous carbon nanomaterial itself, the gas transmission resistance of CH4 is small, and the membrane thickness is thin, thereby improving the permeability of the inorganic composite membrane. Compared with polymer membranes and mixed matrix membranes, the inorganic composite membrane with α-Al3O4 ceramic as the substrate is not affected by the trade-off effect, has high mechanical strength and good separation effect. α-Al3O4 ceramic is used as the substrate because of its high temperature resistance. It is formed into a two-dimensional porous carbon nanosheet inorganic composite membrane in one step with two-dimensional porous carbon nanosheets. Compared with the preparation of mixed matrix membranes, it avoids the defects of uneven dispersion and phase separation of two-dimensional porous carbon nanosheets in the membrane.
[0037] Example 2
[0038] A method for preparing an inorganic composite membrane A for denitrification of natural gas comprises the following steps:
[0039] S1, preparation of two-dimensional porous carbon nanosheet precursor solution;
[0040] The preparation method of the two-dimensional porous carbon nanosheet precursor solution is:
[0041] S1.1, dissolve poloxamer F127 in an appropriate amount of water at 40°C, stir for 1 hour until evenly mixed, to obtain a poloxamer F127 solution; dissolve resorcinol and aldehyde in an appropriate amount of water, mix the poloxamer F127 solution with them and stir evenly; then, add propylamine and stir at a uniform speed, the solution turns white within 0.5 hour; add 1.5M ammonia solution to the white solution, heat to 80°C, stir for 4 hours, to obtain a first solution; wherein, poloxamer F127: resorcinol: propylamine: formaldehyde: ammonia solution: water = 0.1g: 0.22g: 0.03g: 0.292ml: 5ml: 390ml.
[0042] S1.2, take the following raw materials by weight: 100 parts of 0.1 mol / L K4[Fe(CN)6] solution, 30 parts of the first solution in S1.1, and 3 parts of iron-based organosilicon precursor;
[0043] S1.3, mixing and stirring the raw materials described in S1.2 in a water bath at 30° C. for 4 hours to obtain a second solution;
[0044] S1.4, filtering the second solution once through a PTFE filter membrane with a pore size of 0.22 nm, then washing the filtered precipitate with water until the pH value is 6, and collecting the washed precipitate;
[0045] S1.5, mixing the washed precipitate with N-dimethylformamide (DMF) solution to obtain a 0.1 wt. % third solution; the third solution is the two-dimensional porous carbon nanosheet precursor solution.
[0046] Wherein, the preparation method of the iron-based organic precursor is preferably:
[0047] According to weight, 50 parts of methylvinylcyclosiloxane, 0.05 parts of vinylferrocene, 10 parts of 2-propenylphenol, and 220 parts of NN dimethylformamide (DMF) were added to a closed autoclave, stirred evenly and heated to 60°C at the same time, and 0.33 parts of benzoyl peroxide were added and reacted for 1 hour to obtain an iron-based organosilicon precursor. The partial reaction mechanism equation of the iron-based organic precursor is shown as follows:
[0048]
[0049] S2, pretreatment of α-Al3O4 ceramic substrate support layer;
[0050] The surface of the α-Al3O4 ceramic substrate support layer was polished with 800# and 1500# sandpaper successively until the surface was flat under an electron microscope without obvious defects or protrusions; it was cleaned with a pH 3 HCl solution and a pH 8 NaOH solution for 30 minutes each, and then calcined for 6 hours to remove impurities on the surface and inside of the ceramic substrate support layer;
[0051] S3, after cooling the pretreated α-Al3O4 ceramic substrate support layer, heating it to 100°C, keeping it for 1 hour, taking it out and quickly immersing it in a uniformly dispersed two-dimensional porous carbon nanosheet precursor solution for 10 seconds, slowly pulling it up, and repeating the immersion and pulling up for 2 times, drying it at 50°C for 1 hour, and curing it at 100°C for 3 hours to obtain an initial film;
[0052] S4, carbonizing the initial membrane under the carbonization conditions of argon atmosphere at 500° C. for 5 hours to obtain an inorganic composite membrane A for natural gas denitrification containing two-dimensional porous carbon nanosheets.
[0053] Example 3
[0054] A method for preparing an inorganic composite membrane B for denitrification of natural gas comprises the following steps:
[0055] S1, preparation of two-dimensional porous carbon nanosheet precursor solution;
[0056] The method is:
[0057] S1.1, dissolve poloxamer F127 in an appropriate amount of water at 50°C, stir for 1.5 hours until evenly mixed, to obtain a poloxamer F127 solution; dissolve resorcinol and aldehyde in an appropriate amount of water, mix the poloxamer F127 solution with them and stir evenly; then, add propylamine and stir at a uniform speed, the solution turns white within 1.5 hours; add 1.8M ammonia solution to the white solution, heat to 85°C, stir for 7 hours, to obtain a first solution; wherein, poloxamer F127: resorcinol: propylamine: formaldehyde: ammonia solution: water = 0.3g: 0.55g: 0.09g: 0.55ml: 10ml: 750ml.
[0058] S1.2, take the following raw materials by weight: 300 parts of 0.15 mol / L K4[Fe(CN)6] solution, 35 parts of the first solution in S1.1, and 7 parts of iron-based organosilicon precursor;
[0059] S1.3, mixing and stirring the raw materials described in S1.2 in a water bath at 40° C. for 4.2 h to obtain a second solution;
[0060] S1.4, filtering the second solution four times using a PTFE filter membrane with a pore size of 0.32 nm, then washing the filtered precipitate with water until the pH value is 6.5, and collecting the washed precipitate;
[0061] S1.5, mixing the washed precipitate with N-dimethylformamide (DMF) solution to obtain a 5 wt.% third solution; the third solution is the two-dimensional porous carbon nanosheet precursor solution.
[0062] Wherein, the preparation method of the iron-based organic precursor is preferably:
[0063] According to weight, 55 parts of methylvinylcyclosiloxane, 0.35 parts of vinylferrocene, 12 parts of 2-propenylphenol, and 240 parts of NN dimethylformamide (DMF) were added to a closed autoclave, stirred evenly and heated to 65°C at the same time, and 0.55 parts of benzoyl peroxide were added and reacted for 3 hours to obtain an iron-based organosilicon precursor. The partial reaction mechanism equation of the iron-based organic precursor is shown as follows:
[0064]
[0065] S2, pretreatment of α-Al3O4 ceramic substrate support layer;
[0066] The surface of the α-Al3O4 ceramic substrate support layer was polished with 800# and 1500# sandpapers successively until the surface was flat under an electron microscope without obvious defects or protrusions; it was cleaned with a pH 3.5 HCl solution and a pH 8.5 NaOH solution for 50 minutes each, and then calcined for 8 hours to remove impurities on the surface and inside of the ceramic substrate support layer;
[0067] S3, after cooling the pretreated α-Al3O4 ceramic substrate support layer, heating it to 150°C, keeping it for 1.5 hours, taking it out and quickly immersing it in a uniformly dispersed two-dimensional porous carbon nanosheet precursor solution for 20 seconds, slowly pulling it up, and repeating the immersion and pulling up for 3 times, drying it at 60°C for 1.5 hours, and curing it at 150°C for 5 hours to obtain an initial film;
[0068] S4, carbonizing the initial membrane under the carbonization conditions of argon atmosphere at 700° C. for 4 hours to obtain an inorganic composite membrane B for natural gas denitrification containing two-dimensional porous carbon nanosheets.
[0069] Example 4
[0070] A method for preparing an inorganic composite membrane C for denitrification of natural gas comprises the following steps:
[0071] S1, preparing a two-dimensional porous carbon nanosheet precursor solution; the preparation method is as follows:
[0072] S1.1, dissolve poloxamer F127 in an appropriate amount of water at 60°C, stir for 3 hours until evenly mixed, to obtain a poloxamer F127 solution; dissolve resorcinol and aldehyde in an appropriate amount of water, mix the poloxamer F127 solution with them and stir evenly; then, add propylamine and stir at a uniform speed, the solution turns white within 2.5 hours; add 3M ammonia solution to the white solution, heat to 90°C, stir for 6 hours, to obtain a first solution; wherein, poloxamer F127: resorcinol: propylamine: formaldehyde: ammonia solution: water = 0.5g: 1.1g: 0.15g: 1.25ml: 25ml: 1950ml.
[0073] S1.2, take the following raw materials by weight: 500 parts of 0.3 mol / L K4[Fe(CN)6] solution, 40 parts of the first solution in S1.1, and 10 parts of iron-based organosilicon precursor;
[0074] S1.3, mixing and stirring the raw materials described in S1.2 in a water bath at 50° C. for 5 h to obtain a second solution;
[0075] S1.4, filtering the second solution five times using a PTFE filter membrane with a pore size of 0.52 nm, then washing the filtered precipitate with water until the pH value is 7, and collecting the washed precipitate;
[0076] S1.5, mixing the washed precipitate with N-dimethylformamide (DMF) solution to obtain a 10 wt. % third solution; the third solution is the two-dimensional porous carbon nanosheet precursor solution.
[0077] Wherein, the preparation method of the iron-based organic precursor is preferably:
[0078] According to weight, 70 parts of methylvinylcyclosiloxane, 0.56 parts of vinylferrocene, 15 parts of 2-propenylphenol, and 260 parts of NN dimethylformamide (DMF) were added to a closed autoclave, stirred evenly and heated to 70°C at the same time, and 0.79 parts of benzoyl peroxide were added and reacted for 4 hours to obtain an iron-based organosilicon precursor. The partial reaction mechanism equation of the iron-based organic precursor is shown as follows:
[0079]
[0080] S2, pretreatment of α-Al3O4 ceramic substrate support layer;
[0081] The surface of the α-Al3O4 ceramic substrate support layer was polished with 800# and 1500# sandpaper successively until the surface was flat under an electron microscope without obvious defects or protrusions; it was cleaned with a pH 4 HCl solution and a pH 9 NaOH solution for 60 minutes each, and then calcined for 10 hours to remove impurities on the surface and inside of the ceramic substrate support layer;
[0082] S3, after cooling the pretreated α-Al3O4 ceramic substrate support layer, heating it to 170°C, keeping it for 3 hours, taking it out and quickly immersing it in a uniformly dispersed two-dimensional porous carbon nanosheet precursor solution for 30 seconds, slowly pulling it up, and repeating the immersion and pulling up for 5 times, drying it at 70°C for 2 hours, and curing it at 17°C for 6 hours to obtain an initial film;
[0083] S4, carbonizing the initial membrane under the carbonization conditions of 800° C. for 5 hours in an argon atmosphere to obtain an inorganic composite membrane C containing two-dimensional porous carbon nanosheets for natural gas denitrification.
[0084] Figure 1 This is a SEM image of the α-Al3O4 ceramic substrate support layer after pretreatment in Example 4; Figure 2 This is a SEM image of a sample obtained by directly coating the two-dimensional porous carbon nanosheet precursor solution prepared in Example 4 on an α-Al3O4 ceramic substrate support layer and carbonizing it; Figure 3 The SEM image of the surface of the inorganic composite membrane C prepared in Example 4; Figure 3 It can be found that the two-dimensional porous carbon nanosheets are successfully loaded onto the ceramic substrate support layer. Figure 2 The morphology of the two-dimensional porous carbon nanosheets did not change after being loaded onto the ceramic substrate support layer.
[0085] Figure 4 The X-ray diffraction pattern of the surface of the inorganic composite membrane C prepared in Example 4 shows that no characteristic peak of the ceramic substrate support layer appears under XRD. Figure 4 It can be seen that the two-dimensional porous carbon nanosheet inorganic composite membrane prepared by the method of the present invention is loaded more densely on the ceramic substrate support layer.
[0086] The prepared inorganic composite membrane C with different loadings was put into the gas permeation performance test device for testing, among which the gas permeation performance of CH4 was the largest, and the permeation performance of the gas in the membrane was CH4>N2. As can be seen from the figure, with the gradual increase of the loading, the permeation performance of CH4 gradually increased, and it can be seen that it reached the maximum value at 15wt.%, but the CH4 / N2 selectivity also gradually decreased, which is because the permeation performance of N2 also increased with the increase of the loading.
[0087] It should be noted that the above-described specific embodiments can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. Therefore, although the present invention has been described in detail with reference to the drawings and embodiments, those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. In short, all technical solutions and changes that do not deviate from the spirit and scope of the present invention should be included in the protection scope of the patent of the present invention.
Claims
1. A method for preparing an inorganic composite membrane for natural gas denitrification, characterized in that: The steps include: S1, preparation of two-dimensional porous carbon nanosheet precursor solution; S2, pretreatment of the α-Al3O4 ceramic substrate support layer; grinding the surface of the α-Al3O4 ceramic substrate support layer until it is flat under an electron microscope without obvious defects or protrusions; washing it with a pH 3-4 HCl solution and a pH 8-9 NaOH solution for 30-60 minutes each, and then calcining it for 6-10 hours; removing impurities on the surface and inside of the ceramic substrate support layer; S3, cooling the pretreated α-Al3O4 ceramic substrate support layer, heating it to 100-170°C, keeping it for 1-3 hours, taking it out, and quickly immersing it in a uniformly dispersed two-dimensional porous carbon nanosheet precursor solution for 10-30 seconds, slowly pulling it up, and repeating the immersion and pulling up for 2-5 times, drying it at 50-70°C for 1-2 hours, and curing it at 100-170°C for 3-6 hours to obtain an initial film; S4, carbonizing the initial membrane to obtain an inorganic composite membrane for natural gas denitrification containing two-dimensional porous carbon nanosheets.
2. The method for preparing an inorganic composite membrane for denitrification of natural gas according to claim 1, characterized in that: In S1, the preparation method of the two-dimensional porous carbon nanosheet precursor solution is: S1.1, dissolve poloxamer F127 in an appropriate amount of water at 40-60°C, stir for 1-3 hours until uniformly mixed, and obtain a poloxamer F127 solution; dissolve resorcinol and aldehyde in an appropriate amount of water, and mix the poloxamer F127 solution with the water and stir evenly; then, add amine and stir at a uniform speed, and the solution turns white within 0.5-2.5 hours; add ammonia solution with a concentration of 1.5-3.0M to the white solution, heat to 80-90°C, and stir for 4-8 hours to obtain a first solution; wherein, poloxamer F127: resorcinol: propylamine: formaldehyde: ammonia solution: water = (0.1-0.5g): (0.22-1.1g): (0.03- 0.15g):(0.292~1.46ml):(5~25ml):(390~1950ml); the first solution is a resorcinol formaldehyde resin precursor solution; S1.2, take the following raw materials respectively by weight: 100-500 parts of 0.1-0.3 mol / L K4[Fe(CN)6] solution, 30-40 parts of the first solution in S1.1, and 3-10 parts of an iron-based organosilicon precursor; S1.3, mixing and stirring the raw materials described in S1.2 in a water bath at 30°C to 50°C for 4h to 5h to obtain a second solution; S1.4, filtering the second solution 1 to 5 times using a PTFE filter membrane with a pore size of 0.22 nm to 0.52 nm, then washing with water until the pH value is 6 to 7, and collecting the precipitate; S1.5, mixing the precipitate with a NN dimethylformamide (DMF) solution to obtain a 0.1-10 wt. % third solution; the third solution is the two-dimensional porous carbon nanosheet precursor solution.
3. The method for preparing an inorganic composite membrane for denitrification of natural gas according to claim 2, characterized in that: The preparation method of the iron-based organosilicon precursor is as follows: 50-70 parts of methylvinylcyclosiloxane, 0.05-0.56 parts of vinylferrocene, 10-15 parts of 2-propenylphenol, and 220-260 parts of NN dimethylformamide (DMF) are added into a closed high-pressure reactor, stirred evenly and heated to 60-70°C at the same time, and then 0.33-0.79 parts of benzoyl peroxide are added, and the reaction is carried out for 1-4 hours to obtain the iron-based organosilicon precursor.
4. The method for preparing an inorganic composite membrane for denitrification of natural gas according to claim 1, characterized in that: The initial film carbonization condition of S4 is to maintain the temperature at 500-800° C. for 2-5 hours in an argon atmosphere.
5. The method for preparing an inorganic composite membrane for denitrification of natural gas according to claim 1, characterized in that: In the above-mentioned S2, when grinding the α-Al3O4 ceramic substrate support layer, 800# and 1500# sandpapers are used successively for grinding.
6. The method for preparing an inorganic composite membrane for denitrification of natural gas according to claim 1, characterized in that: In S3, the uniformly dispersed two-dimensional porous carbon nanosheet precursor solution is a two-dimensional porous carbon nanosheet precursor solution uniformly dispersed by ultrasound.
7. The method for preparing an inorganic composite membrane for denitrification of natural gas according to claim 3, characterized in that: The partial reaction mechanism equation of the iron-based organosilicon precursor is:
Citation Information
Patent Citations
Two-dimensional porous carbon nanosheet mixed substrate membrane and preparation method thereof
CN110385048A
Method of making nanomaterials from a renewable carbon source
WO2020226620A1